2012
DOI: 10.1111/j.1365-2893.2011.01570.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe transaminitis after interferon–ribavirin therapy in HIV/HCV‐coinfected patients: influence of a sustained HCV response

Abstract: Chronic hepatitis C is an independent risk factor for severe drug hepatotoxicity. Successful treatment of chronic hepatitis C may modulate drug hepatotoxicity, as it is associated with a decline in hepatic enzyme release and halts fibrosis progression in HIV/HCV-coinfected patients. The aim of this study was to determine biological and/or clinical determinants of alanine aminotransferase and/or aspartate aminotransferase elevation (>five-fold above the upper limit of normal in patients with normal baseline lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Several studies have assessed the impact of interferon therapy on DM, either as a protective factor or as a risk factor . SVR in HCV infected patients has been associated with both regression of severe transaminitis, steatosis, IR and the prevention of DM development . In a Spanish cohort of 1625 HIV/HCV coinfected patients treated with IFN and ribavirin, SVR (n = 592) after a median 5‐year follow‐up was associated with a significant decrease in the hazard ratio for DM (sHR 0.57 [95% CI, 0.35‐0.93] P = 0.024) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have assessed the impact of interferon therapy on DM, either as a protective factor or as a risk factor . SVR in HCV infected patients has been associated with both regression of severe transaminitis, steatosis, IR and the prevention of DM development . In a Spanish cohort of 1625 HIV/HCV coinfected patients treated with IFN and ribavirin, SVR (n = 592) after a median 5‐year follow‐up was associated with a significant decrease in the hazard ratio for DM (sHR 0.57 [95% CI, 0.35‐0.93] P = 0.024) .…”
Section: Discussionmentioning
confidence: 99%
“…34 SVR in HCV infected patients has been associated with both regression of severe transaminitis, steatosis, IR and the prevention of DM development. 14,18,19,[34][35][36] In a Spanish cohort of 1625 HIV/HCV coinfected patients treated with IFN and ribavirin, SVR (n = 592) after a median 5-year follow-up was associated with a significant decrease in the hazard ratio for DM (sHR 0.57 [95% CI, 0.35-0.93] P = 0.024). 19 In a Swiss cohort, HCV-treated patients without SVR (n = 281) had a 4-fold higher risk of DM compared to those with SVR (n = 345).…”
Section: By Univariate Analysis (mentioning
confidence: 99%
“…Indeed, it is well established that HCV SVR markedly lessens the risk of severe transaminitis during antiretroviral therapy and reduces the risk of developing severe endstage liver disease [7,16]. One possible reason for this could be a better tolerance of antiretroviral drugs, which in turn leads to a higher rate of HIV SVS.…”
Section: Discussionmentioning
confidence: 99%
“…Early HAART initiation is associated with less severe liver disease [2,6]. However, chronic hepatitis C is an independent risk factor for severe antiretroviral hepatotoxicity, with a three-fold higher risk of grade 3 or 4 transaminitis [7][8][9]. Despite the higher risk of HAART hepatotoxicity in this population, most studies have not shown a negative impact of HCV infection on HIV virologic control [10,11].…”
Section: Introductionmentioning
confidence: 99%